2022
DOI: 10.3390/diagnostics12102339
|View full text |Cite
|
Sign up to set email alerts
|

Endometrioid Carcinomas of the Ovaries and Endometrium Involving Endocervical Polyps: Comprehensive Clinicopathological Analyses

Abstract: While synchronous ovarian and endometrial endometrioid carcinomas (ECs) have long been described in the literature, ovarian or endometrial EC involving concomitant endocervical polyp (ECP) has not yet been reported. This study aimed to investigate the histological types and prevalence of gynecological tumors co-existing with ECP and to comprehensively analyze the clinicopathological characteristics of ovarian and endometrial ECs involving ECPs. We searched for ECP cases associated with premalignant lesions or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The Proactive Molecular Risk Classifier for Endometrial Cancer introduced four subgroups of EC: (1) DNA polymerase epsilon, catalytic subunit ( POLE )-mutant subgroup, harboring mutations in the exonuclease domain in exons 9–14; (2) MMRd subgroup, showing the loss of expression for one or more MMR proteins; (3) p53-abnormal subgroup, demonstrating aberrant p53 expression pattern indicating pathogenic TP53 mutation; and (4) no specific molecular profile (NSMP) subgroup [ 63 , 64 , 65 ]. Even though the vast majority of NSMP ECs is low-grade endometrioid carcinoma, the NSMP subgroup also encompasses high-grade EC, clear cell carcinoma, undifferentiated carcinoma, carcinosarcoma, and MLA [ 36 , 40 , 50 , 51 , 53 , 57 , 65 , 66 , 67 , 68 ]. In this study, the majority of MLA cases harbored activating KRAS mutations but not POLE -mutant signatures, MMR deficiency, or TP53 mutation; confirming that these cases belong to the NSMP subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Proactive Molecular Risk Classifier for Endometrial Cancer introduced four subgroups of EC: (1) DNA polymerase epsilon, catalytic subunit ( POLE )-mutant subgroup, harboring mutations in the exonuclease domain in exons 9–14; (2) MMRd subgroup, showing the loss of expression for one or more MMR proteins; (3) p53-abnormal subgroup, demonstrating aberrant p53 expression pattern indicating pathogenic TP53 mutation; and (4) no specific molecular profile (NSMP) subgroup [ 63 , 64 , 65 ]. Even though the vast majority of NSMP ECs is low-grade endometrioid carcinoma, the NSMP subgroup also encompasses high-grade EC, clear cell carcinoma, undifferentiated carcinoma, carcinosarcoma, and MLA [ 36 , 40 , 50 , 51 , 53 , 57 , 65 , 66 , 67 , 68 ]. In this study, the majority of MLA cases harbored activating KRAS mutations but not POLE -mutant signatures, MMR deficiency, or TP53 mutation; confirming that these cases belong to the NSMP subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the majority of MLA cases harbored activating KRAS mutations but not POLE -mutant signatures, MMR deficiency, or TP53 mutation; confirming that these cases belong to the NSMP subgroup. Since the biological behavior of uterine MLA is consistently described as aggressive [ 36 , 67 , 69 ], the inclusion of this entity in the high-risk non-endometrioid group appears to be justified. Several studies have identified that the high expression of the L1 cell adhesion molecule (L1CAM) and CTNNB1 mutation can add significant prognostic information to the molecular classification of EC [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostaining was performed using whole-tissue sections containing >80% viable tumor tissue, as previously described [24][25][26][27][28][29][30][31][32]. In brief, 4 µm thick FFPE tissue sections were deparaffinized and rehydrated using a xylene and alcohol solution.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining for Ki-67 was performed using whole-tissue sections as described previously [16][17][18][19][20][21][22][23][24]. For each case, the most representative slide containing >80% of viable tumor tissue was chosen for immunostaining.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%